Impact of cold-wire gas metal arc welding (CW-GMAW) parameters on microstructure and microhardness characteristics in repairing S275JR structural steel - Musa, Zahraddeen; Ganguly, Supriyo; Suder, Wojciech; Igwemezie, Victor; Rajamudili, Kuladeep (Springer, 2025)
This study investigates the influence of adding a cold wire during gas metal arc welding (CW-GMAW) for repair of S275JR structural steel. The research is aimed at improving repair productivity through increased deposition rates with enhanced performance. During weld repair, multiple passes induce large number of thermal cycles and a huge thermal gradient on the material which has an adverse effect on the material’s properties. This is largely due to the microstructural changes that occur during the process. In this work, a systematic approach has been adopted to explore the effects of varying gas metal arc welding (GMAW) parameters, including wire feed rate, welding current, voltage, travel speed, and specifically cold-wire feed speed on the heat affected zone (HAZ) microstructure and hardness. Macrostructural examination highlights significant alterations in the heat affected zone (HAZ) region, with marked microhardness changes in both WM and HAZ. Cold-wire addition led to a reduction in the HAZ area, depth of weld metal penetration, and significantly reduced the impact of imposing thermal cycles on the HAZ of the welded samples. Additionally, microstructural analysis was conducted using a standard optical microscope to correlate the observed hardness variations with microstructural transformations in the weld metal and heat affected zone (HAZ). The findings reveal that specific combinations of CW-GMAW parameters can significantly influence the microstructure and thereby hardness, suggesting that with careful control of these parameters, it would be possible to do faster repair with minimal loss of integrity for critical structural steels.
Keywords: 4014 Manufacturing Engineering; 40 Engineering